DISCRIMINANT MODELS POSSIBILITIES DISEASE AND FEATURES COURSE OF ACNE IN GIRLS PODILSKIY REGION OF UKRAINE DEPENDING ON THE SIZE BODY - Дмитренко, С.В.; Маєвський, О.Є.; Макарчук, І.М. (World of Medicine and Biology, 2016)
Aim of our work – build discriminant model capabilities features and disease acne based on anthropometric indices of Podillya girls.Materials and methodsDone clinical laboratory and anthropological examination of 116 patients with acne of Podillya girls aged from 16 to 20 years. The obtained results are compared with data anthropo-somatotypological survey of 160 apparently healthy girls of similar age and region of residence with data bank Scientific and Research Center Vinnitsa National Medical University named after Pirogov.Used the following methods: general clinical - to verify the diagnosis of acne; anthropometry by the method V. Bunak in modification P. Shaparenko; somatotype determination by the method J. Carter and B. Heath. Construction of discriminant models held in license statistical package "STATISTICA 6.0".Results. DiscussionsAs in previous studies in boys received discriminant equations permit with high probability based on accounting indicators morphological constitution divide girls into groups of healthy and patients with acne in general (model correct in 94.2% of cases, statistics Wilks lambda = 0.276 and girls in 94.9% of cases, statistics Wilks lambda = 0.348 in boys), in healthy and patients with mild acne severity (model correct in 95.3% of cases, statistics Wilks lambda = 0.297 in girls and 95.3% of cases, statistics Wilks lambda = 0.420 in boys) and on healthy and patients with acne of moderate severity (model correct in 98.0% of cases, statistics Wilks lambda = 0.322 in girls and 95.6% of cases, statistics Wilks lambda = 0.407 in boys). As in boys, discriminant analysis revealed in girls insignificant discrimination on somatotypological and anthropometric indicators between patients with acne mild and moderate severity (girls Statistics Wilks lambda = 0.850, and the boys - 0.801), which is valid only in 64.0 % of cases (boys - in 71.2% of cases).As in youths to discriminant equations with average values of discriminant function in girls included 6-7 anthropometric indicators. However, if the young men of the similar patterns in all three cases included TSFF on the chest and shoulder width, the in girls – TSFF of chest, cross lower chest size, shoulder width and outer conjugate. In addition, if the youths had two models included cross lower chest size, girth chest on inspiration, girth of hand and TSFF on the hip, in girls - TSFF on shin and on the back of the shoulder. Thus, performance TSFF on the chest and shoulder width entered into the discriminant in all 6 models with average level of discriminant function as in boys and in girls, and the index cross the lower chest size - include 5 of 6 of these models.
Keywords: acne; girls; discriminant model; anthropometry